Age-related lung tissue remodeling due to the local distribution of MMP-2, TIMP-2, TGF-β and Hsp70. (19th May 2018) - Vitenberga, Z; Pilmane, M
Abstract: Lung tissue remodeling requires complex interactions of matrix metalloproteinases (MMPs), tissue inhibitors of metalloproteinases (TIMPs), transforming growth factor (TGF) family and heat shock protein 70 (Hsp70). We evaluated the appearance and distribution of MMP-2, TIMP-2, TGF-β1 and Hsp70 in lung tissue using immunohistochemistry. Stained structures were graded semiquantitatively. Overall, more MMP-2, TIMP-2, TGF-β1 and Hsp70 were observed in bronchial cartilage, bronchial and alveola repithelium, and among alveolar macrophages. We evaluated mostly alveolar macrophages, bronchial epithelial cells and mucosal fibroblasts stained for TGF-β1, MMP-2 and TIMP-2. We also assessed strong or moderate correlations between numbers of cells containing TGF-β1, MMP-2, TIMP-2 in patients ≥ 60 years old. The presence of less TGF-β1 and more MMP-2, TIMP-2 and Hsp70 containing cells in all tissue groups indicated that local regulation was more dependent on MMP-2, TIMP-2 and Hsp70 distribution. Fewer TIMP-2, Hsp70 and TGF-β1 immunoreactive cells in younger individuals and increased expression of Hsp70 in elderly individuals demonstrated the influence of aging in lung remodeling. Findings of MMP-2, TIMP-2 and TGF-β1 immunoreactive cells in elderly individuals indicate lung remodeling due to aging.